Critical Thinking Ability of Vocational Students in Solving Systems of Equations With Three Variables Story Problems: A Review Based on Learning Style - Maulidiyah, Rizky; Lestari, Nurcholif Diah Sri; Oktavianingtyas, Ervin; Trapsilasiwi, Dinawati; Monalisa, lioni Anka (Universitas Negeri Surabaya, 2024)
This study aims to describe the critical thinking skills of vocational students in solving the story problem of the equation system with 3 variables in the context of auditory, visual, and kinesthetic learning styles. This type of research is descriptive qualitative. Subject selection was based on the results of the learning style questionnaire consisting of six students in class XI with details of two students for each learning style. The research data were collected through critical thinking skills tests and interviews. The results showed that students with visual, auditory, and kinesthetic learning styles had different critical thinking skills. Students with visual learning styles can fulfill the aspects of interpretation, analysis, evaluation, explanation, and self-regulation. The inference aspect cannot be fulfilled by visual students. Students with auditory learning styles can fulfill the aspects of interpretation, analysis, evaluation, and explanation. The aspects of inference and self-regulation have not been fulfilled by auditory students. Students with kinesthetic learning styles can fulfill the aspects of interpretation, analysis, and evaluation. The aspects of inference, explanation, and self-regulation have not been fulfilled by kinesthetic students. All students have the potential to improve critical thinking skills, one of which is that teachers can ask open questions or questions that raise students' awareness so that they can have a positive impact on critical thinking skills.